Sarojini Naidu : Treatment of Nature - Chouhan, Sandhya (Journal of Advanced Research in English & Education, 2021)
Sarojini Naidu has not been a profound poetess. Her poetry is not concerned with deep and philosophical questions of God, Man and Universe. It was her desire for beauty that made her a poetess. Therefore, she is sensitive to all forms of beauty. Nature’s beauty has special charm for her and excites her poetic innagination. How to cite this article:  Chouhan S. Sarojini Naidu : Treatment of Nature. J Adv Res Eng & Edu 2019; 4(4): 12-14. DOI: https://doi.org/10.24321/2456.4370.201910